How “Omics” Studies Contribute to a Better Understanding of Fuchs’ Endothelial Corneal Dystrophy - Erika Prašnikar; Spela Stunf Pukl (Current Issues in Molecular Biology)
Fuchs’ endothelial corneal dystrophy (FECD) is a progressive eye disease characterized by accelerated loss of endothelial cells and the development of focal excrescence (guttae) on Descemet’s membrane, resulting in cornea opacity and vision deterioration. The development of FECD is assumed to be due to the interplay between genetic and environmental factor risks, causing abnormal extracellular-matrix organization, increased oxidative stress, apoptosis and unfolded protein response. However, the molecular knowledge of FECD is limited. The development of genome-wide platforms and bioinformatics approaches has enabled us to identify numerous genetic loci that are associated with FECD. In this review, we gathered genome-wide studies (n = 31) and sorted them according to genomics (n = 9), epigenomics (n = 3), transcriptomics (n = 15), proteomics (n = 3) and metabolomics (n = 1) levels to characterize progress in understanding FECD. We also extracted validated differentially expressed/spliced genes and proteins identified through comparisons of FECD case and control groups. In addition, highlighted loci from each omics layer were combined according to a comparison with similar study groups from original studies for downstream gene-set enrichment analysis, which provided the most significant biological pathways related to extracellular-matrix organization. In the future, multiomics study approaches are needed to increase the sample size and statistical power to identify strong candidate genes for functional studies on animal models and cell lines for better understanding FECD.